2015
DOI: 10.1080/02763869.2015.1082390
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Marketing Orientation in Hospital Library Services: A Case Report

Abstract: When the four Providence Health & Services libraries in Oregon regionalized services and resources, the transition, which was originally met with apprehension from some library users, turned out to be a resounding success. Despite a loss of two-thirds of the professional staff and a decreased budget, the new regionalized library experienced an increase in business and recognition. While many factors contributed to the success, a creative marketing and outreach campaign was a key component. This column describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…All those who had tried this approach agreed it was highly successful. Whilst none specifically labelled it as ‘marketing orientation’, the idea that they are focusing on specific resources that could help a certain group of people is one that has definitely seen a large amount of success (Delawska‐Elliott et al, 2015, p. 483). Whilst this was seen as an extremely successful way to market, it was also the most time consuming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All those who had tried this approach agreed it was highly successful. Whilst none specifically labelled it as ‘marketing orientation’, the idea that they are focusing on specific resources that could help a certain group of people is one that has definitely seen a large amount of success (Delawska‐Elliott et al, 2015, p. 483). Whilst this was seen as an extremely successful way to market, it was also the most time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of marketing in libraries is undefined with literature identifying marketing as everything and everywhere (Gupta, 2016, p. 126), or a more ‘narrative based’ approach placing emphasis on the value the library can provide for the user (Urquhart, 2015, p. 88; Germano, 2010; Thorpe & Bowman, 2013). As Delawska‐Elliott et al (2015) have shown, there is increasing conflict over whether a more streamlined marketing approach conducted by developing a ‘marketing orientation and a marketing culture’ is the most effective (p. 483). Velasquez and Campbell‐Meier (2018) believe libraries can evidence this ‘outcome based marketing’ by demonstrating how they are fulfilling ‘mission or vision statements’ and achieving this by setting SMART criteria (p. 125).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Service promotion. Promotion increases user awareness and efficient use of the services and resources available [34]. The library serves not only clinical staff, but may serve others, including: [35,36].…”
Section: Standardmentioning
confidence: 99%
“…Interlibrary loan, document delivery, and onsite and remote access to subscription resources, as well as copying, faxing and printing of biomedical literature must adhere to vendor license agreements, publishing contracts, and federal and/or international copyright legislation. In addition, the hospital library adheres to the Health Information Portability and Accountability Act (HIPAA) and patient confidentiality when assisting patients, families, health care providers and others who may use the library or any of its services or resources [34,35]. Intent.…”
Section: Standardmentioning
confidence: 99%
“…Few important studies that have been reviewed with regard to the marketing of products and services by health libraries are summarized as follows: Delawska-Elliott et al (2015) explained “when the four Providence Health and Services libraries in Oregon regionalized services and resources, the transition, which was originally met with apprehension from some library users, turned out to be a resounding success. Despite a loss of two-thirds of the professional staff and a decreased budget, the new regionalized library experienced an increase in business and recognition.…”
Section: Literature Reviewmentioning
confidence: 99%